Pemodelan Pasut di Indonesia Timur Menggunakan Data Asimilasi dari Altimetri, Stasiun Pasut, dan Model Hidrodinamika - Misfallah Nurhayati; Dudy Darmawan Wijaya (LPPM Politeknik Aceh Selatan, 2024)
Tides play a crucial role in various coastal and marine activities. Despite numerous tidal models developed in Indonesia, modeling tides in shallow waters with complex topographies remains challenging, particularly in the Eastern Indonesian Sea. This study aims to develop a high-accuracy tidal model for Eastern Indonesian sea using data assimilation techniques integrating observational data and ocean dynamics model. The study tested various scenarios, including different numbers of tide gauge observations, representers, and decorrelation length values in dynamic equations. By assimilating data from altimetry, tide gauges, and hydrodynamic models, significant improvements in model accuracy were achieved. Results show that of the 11 validator tide stations, while the rest stations have the predicted RMS values below 16 cm, and seven stations have the predicted RMS values below 9 cm. These findings highlight the potential use of assimilation technique for accurate tidal predictions in shallow waters with complex topographies, enhancing the safety and efficiency of coastal and marine activities in Eastern Indonesia.